1992
DOI: 10.1037/0022-3514.62.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Why people self-verify.

Abstract: Why do people choose interaction partners who see them as they see themselves? Self-verification theorists propose that a desire to bolster perceptions of predictability and control underlies such activities. In contrast, advocates of positivity strivings argue that people choose such interaction partners in the hope of making themselves feel good. Two studies tested these competing explanations by examining the spontaneous verbalizations of participants as they chose interaction partners. The results suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
416
0
7

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(454 citation statements)
references
References 41 publications
22
416
0
7
Order By: Relevance
“…Although language use is often assumed to represent a relatively spontaneous behaviour (Swann, Stein-Seroussi, & Giesler, 1992), it is arguably not as spontaneous as behaviours that occur at early, lower-order stages of attentional processing. Recent research has demonstrated that once attention has been directed toward an attractive member of the preferred sex, perceivers find it difficult to disengage (e.g., Maner, Gailliot, & DeWall, 2007), unless recently prompted to think of their love for their partner (Maner, Rouby, & Gonzaga, 2008).…”
Section: Overview and Hypothesesmentioning
confidence: 99%
“…Although language use is often assumed to represent a relatively spontaneous behaviour (Swann, Stein-Seroussi, & Giesler, 1992), it is arguably not as spontaneous as behaviours that occur at early, lower-order stages of attentional processing. Recent research has demonstrated that once attention has been directed toward an attractive member of the preferred sex, perceivers find it difficult to disengage (e.g., Maner, Gailliot, & DeWall, 2007), unless recently prompted to think of their love for their partner (Maner, Rouby, & Gonzaga, 2008).…”
Section: Overview and Hypothesesmentioning
confidence: 99%
“…Moreover, people are highly motivated to express their self-identities, often through consumption experiences (Aaker 1999;Belk 1988;Berger and Heath 2007;Celsi, Rose, and Leigh 1993;Shavitt, Lowrey, and Han 1992;Vazire and Gosling 2004). They are also highly motivated to maintain a consistent and stable self-identity and will reject information that challenges this self-identity (Swann 1987;Swann, Stein-Seroussi, and Giesler 1992). In this light, we propose that people will be especially reluctant to artificially enhance themselves in ways that are believed to alter their fundamental selves.…”
mentioning
confidence: 99%
“…The main mechanism linking over-disidentification with anti-organizational crimes is self-verification (Burke 1991, Burke and Harold 2005, Swann 1983, Swann and Read 1981, Swann et al 1992. As with overidentification, over-disidentifiers still see their organizations as highly central to their self-definitions-though there is less blurring of person and organization, as is the case with over-identifiers.…”
Section: Anti-organizationalmentioning
confidence: 99%
“…Self-expansion argues that an individual's self-construal includes one's organizational membership. And according to self-verification theory (Burke 1991, Burke and Harold 2005, Swann 1983, Swann and Read 1981, Swann et al 1992, once individuals form self-views, they work to stabilize them by seeking and embracing experiences that match their self-views and by avoiding or rejecting experiences that challenge them. And when faced with a challenging situation that potentially threatens individuals' view of the self, they are motivated to respond to this situation both affectively and behaviorally.…”
Section: Over-identificationmentioning
confidence: 99%